The impact of an early intervention home-based program on body composition in preterm-born preschoolers with very low birth weight - Fernandes, Rafael Oliveira; Bernardi, Juliana Rombaldi; da Fonseca, Júlia Delgado; Gomes da Silva, Franciéle; Procianoy, Renato Soibelmann; Silveira, Rita C. (Frontiers in Nutrition, 2022)
Background and aims: Early child interventions focused on the family prevent neurodevelopmental and behavioral delays and can provide more knowledge regarding responsive feeding, thus creating learning opportunities to promote better quality nutrition and preventing failure to thrive. The aim is to verify the impact of a continuous program of early home-based intervention on the body composition of preschool infants who were born preterm with very low birth weight (VLBW). Method: This is a longitudinal analysis from a randomized controlled trial including VLBW preterm children, born in a tertiary hospital in Southern Brazil and followed up at the high-risk institutional ambulatory clinic. Participants were divided into Intervention Group (IG): skin-to-skin care with the mother (kangaroo care), breastfeeding policy, and tactile-kinesthetic stimulation by mothers until hospital discharge. Subsequently, they received a program of early intervention with orientation and a total of 10 home visits, independently from the standard evaluation and care that was performed following the 18 months after birth; Conventional Group (CG): standard care according to the routine of the newborn intensive care unit (NICU), which includes kangaroo care, and attending to their needs in the follow-up program. Body composition estimation was performed using bioelectrical impedance analyses (BIA), physical activity and feeding practices questionnaires were evaluated at preschool age, as well as anthropometric measurements and biochemical analysis. Results: Data of 41 children at 4.6±0.5 years-old were evaluated (CG n=21 and IG n=20). Body weight, height, body mass index, waist and arm circumferences, and triceps and subscapular skinfold did not differ between groups. The IG presented higher segmented fat-free mass (FFM) when compared to the CG (right arm FFM: 0.74 versus 0.65 Kg, p=0.040; trunk FFM: 6.86 versus 6.09Kg, p=0.04; right leg FFM: 1.91 versus 1.73 Kg, p=0.054). Interaction analyses showed that segmented FFM and FFM Index were associated with higher iron content in the IG. In the CG, interaction analyses showed that increased visceral fat area was associated with higher insulin resistance index. Conclusions: An early intervention protocol from NICU to a home-based program performed by the mothers in VLBW preterm children of low-income families present a small effect on FFM.